Emotions and Virtues in Feature Writing: The Alchemy of Creating Prize-Winning Stories, Jennifer Martin (2021). Issue 2 (1st November 2021) - Vatsikopoulos, Helen
Review of: Emotions and Virtues in Feature Writing: The Alchemy of Creating Prize-Winning Stories, Jennifer Martin (2021)Cham: Palgrave Macmillan, 270 pp., ISBN 978-3-03062-977-9, h/bk, €89.99ISBN 978-3-03062-978-6, e-book, €74.89